1993
DOI: 10.1109/55.215175
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of N/sub 2/O-annealed MOSFET characteristics in response to dynamic oxide stressing

Abstract: The performance of n-MOSFETs with furnace N,O-annealed gate oxides under dynamic Fowler-Nordheim bipolar stress was studied and compared with that of conventional oxide (OX). Time-dependent dielectric breakdown at high frequency was shown to be improved for the N,O-annealed devices compared with that for devices with OX. In addition, a smaller V, shift for nitrided samples after stress was found. The shift decreased with increasing stressing frequency and annealing temperature. Measurements of both G , and Dit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…High quality thin oxide devices are necessary in VLSI technology. Many works had been done on how to grow high quality oxide layer, such as nitride oxides [1], reoxided nitrided oxides [2,3], or N20 oxides [4,5], etc. In addition, a few works [6,7] reported that the post-metallization annealing (PMA) process can also affect the performance of MOS devices.…”
Section: Introductionmentioning
confidence: 99%
“…High quality thin oxide devices are necessary in VLSI technology. Many works had been done on how to grow high quality oxide layer, such as nitride oxides [1], reoxided nitrided oxides [2,3], or N20 oxides [4,5], etc. In addition, a few works [6,7] reported that the post-metallization annealing (PMA) process can also affect the performance of MOS devices.…”
Section: Introductionmentioning
confidence: 99%